1993
DOI: 10.1136/pgmj.69.812.419
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular investigations in diabetes mellitus

Abstract: Summary: This paper reviews the current literature concerning the different investigative modalities available to assess the microcirculation in diabetic microangiopathy. The advantages and disadvantages of the different invasive and noninvasive methods available are presented objectively. We have concentrated on the tests that provide a quantitative assessment of the microcirculation, including laser Doppler fluxmetry, capillary microscopy, plethysmography, transcutaneous oximetry and radioactive isotope clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The result is an increase in microvascular flow and capillary pressure [25], which subsequently induces an endothelial injury response. In a later stage, microvascular sclerosis does occur as a result of the thickening of the capillary basement membrane due to long-term structural adaptation and remodeling [82,83]. The elasticity of the vessel walls is reduced, which physically limits vasodilation.…”
Section: Haemodynamic Hypothesismentioning
confidence: 99%
“…The result is an increase in microvascular flow and capillary pressure [25], which subsequently induces an endothelial injury response. In a later stage, microvascular sclerosis does occur as a result of the thickening of the capillary basement membrane due to long-term structural adaptation and remodeling [82,83]. The elasticity of the vessel walls is reduced, which physically limits vasodilation.…”
Section: Haemodynamic Hypothesismentioning
confidence: 99%
“…The 133 Xenon-clearance technique (Chittenden and Shami 1993) is a reliable but invasive method that can be used to determine blood flow during external loading (Daly et al 1976). Using this method Daly et al (1976) found blood flow to reduce rapidly for pressures up to 10mmHg and then at a slower rate until cessation at systolic pressure.…”
Section: Assessing the Affects Of Pressure On The Microcirculationmentioning
confidence: 99%
“…The laser Doppler technique was identified as most appropriate for this application because of the fast response time, the small size and flexible geometry of the probe head and ability to obtain data continuously and noninvasively. The technique has also been used successfully, in other studies of cutaneous blood flow in diabetes mellitus (Chittenden and Shami 1993). However, commercial laser Doppler systems were found to be unsuitable, because the use of fibre optic connections to the probe head resulted in the Doppler signal being swamped by movement artefact noise.…”
Section: Re-evaluation Of Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage caused by hyperglycemia leads to important implications for transcapillary transport and the cirulation of endothelial products like the Von Willebrand factor and the angiotensin converter enzymes that can lead to platelet aggregation abnormalities and interfere in the inflammatory process of the healing 15 . Many of the complications of diabetes are the result of damage caused to the microcirculation vessels 24 . High glucose concentrations activate the aldose reductate which converts glucose to sorbitol.…”
Section: Introductionmentioning
confidence: 99%